School director training and Educational Inspection - Antúnez, Serafín; Silva, Patricia (Avances en Supervisión Educativa, 2020)
Based on a review of the most characteristic functions associated with the performance of the inspectorial function, typical of a democratic professional model, we highlight the importance that we attach to those that have the greatest impact on the professional development of the collective of school directors: training and advice. Taking into account the researches of the doctoral thesis about Educational Inspection Service in Spain between 2008 and 2019 and those found through a review of the literature in the same period, it is clear that our subject of study appears still weak as a central focus of analysis or it deserves tangential and anecdotal consideration. In this article, we aim to provide an overview of practical reflections and proposals for action aimed at improving the performance of these functions by the collective inspector.